2022
DOI: 10.1111/gcb.16495
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling

Abstract: The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 120 publications
0
4
1
Order By: Relevance
“…According to Li et al. (2023), the TP ERR using UTrack with ERA5 data is about 76.2% (their Table 2), slightly different from our estimate of 79.7% due to possible differences in the exact study region, grid size, and other factors. Based on the evaluation of the two models in simulating the fate of TP evaporation, we cautiously suggest that WAM2Layers may be a better model for this region.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Li et al. (2023), the TP ERR using UTrack with ERA5 data is about 76.2% (their Table 2), slightly different from our estimate of 79.7% due to possible differences in the exact study region, grid size, and other factors. Based on the evaluation of the two models in simulating the fate of TP evaporation, we cautiously suggest that WAM2Layers may be a better model for this region.…”
Section: Discussioncontrasting
confidence: 99%
“…ET in dominates the ET moisture over the TP, especially in summer the ET in ratio reaches up to 73.1%. Recently, based on EAR5, Li et al (2022b) also found the same seasonality of the contribution of ET to the TP itself and eastern China, although the uncertainty of ERA5 precipitation might exert uncertainty on results than regional climate simulations (Xu & Gao, 2019). The similarities of 2014 and multiyear average in our study, as well as our findings and results of other groups demonstrate the representative of the normal year 2014 in the spatial distribution and seasonal variation of ET for multiyears average.…”
Section: Resultsmentioning
confidence: 89%
“…These can be interpreted in the way that, grasslands could enhance the precipitation contribution directly through evaporation (Y. Li et al, 2023). Since evaporation from grassland is probably driven by energy availability as proposed by Jansen et al (2023), net radiation as indication of energy availability is compared between different land-use categories, and it turns out to be the possible drivers of stronger evaporation in grasslands as expected.…”
Section: Characteristics Of Prrmentioning
confidence: 94%